The Second Chebyshev Wavelets for Solving the Fractional Langevin Equation - Bargamadi, E.; Torkzadeh, L.; Nouri, K. (Numerical analysis and applications, 2025)
This paper aims to provide an efficient numerical method based on the second Chebyshev wavelets for solving the fractional Langevin equation. Applying this operational matrix of fractional-order integration of second Chebyshev wavelets converts the original problem into a system of algebraic equations, which could be solved by the Newton method. After analyzing the method, the error bound is estimated. Moreover, the method’s efficiency through a few numerical examples is evaluated.